2020
DOI: 10.1098/rsos.192100
|View full text |Cite
|
Sign up to set email alerts
|

Apis ceranagut microbiota contribute to host health though stimulating host immune system and strengthening host resistance toNosema ceranae

Abstract: Gut microbial communities play vital roles in the modulation of many insects' immunity, including Apis mellifera . However, little is known about the interaction of Apis cerana gut bacteria and A. cerana immune system. Here in this study, we conducted a comparison between germ-free gut microbiota deficient (GD) workers and conventional gut community (CV) workers, to reveal the possible impact of gut microbiota on the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…4), which are common opportunistic bacterial pathogens in insects (81,82). Adult butterflies may be similar to pyrrhocorid bugs, tsetse flies and social bees, in which gut bacteria provide an important layer of defense against related parasites and pathogens (83)(84)(85)(86)(87). Importantly, colonization resistance can readily evolve even in symbioses lacking strong host-microbe specificity (88), such as that between heliconiines and their adult-stage microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…4), which are common opportunistic bacterial pathogens in insects (81,82). Adult butterflies may be similar to pyrrhocorid bugs, tsetse flies and social bees, in which gut bacteria provide an important layer of defense against related parasites and pathogens (83)(84)(85)(86)(87). Importantly, colonization resistance can readily evolve even in symbioses lacking strong host-microbe specificity (88), such as that between heliconiines and their adult-stage microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial loads of workers were determined by quantitative PCR (qPCR) using universal bacterial 16S rRNA primers (F: 5′-AGAGTTTGATCCTGGCTCAG-3,′ R: 5′-CTGCTGCCTCCCGTAGGAGT-3′). Sampled guts of workers were obtained according to the protocol described by Wu et al (2020a) and their DNA using TIANamp Stool DNA Kit (Tiangen Biotech Co., Ltd., Beijing, China) according to the manufacturer’s protocol. The StepOne Plus real time PCR system was used for the absolute quantification of 16S rRNA copy number.…”
Section: Methodsmentioning
confidence: 99%
“…Previous documentations showed that microsporidian infection significantly increased the mortality of both A. mellifera and A. cerana workers [7,17]. Paris et al [16] assessed the survival rate and eating behavior of western bee workers infected by N. ceranae for 1–22 days, and found that the survival rate of infected workers was significantly lower than that of un-infected workers.…”
Section: Discussionmentioning
confidence: 99%